The Effect of Industrial Wastewater on Seawater Pollution - Zainab Amer Mohammed; Ruqaia AbuAjila Sheliq; Amal Ali Sanun (Surman Journal of Science and Technology, 2024)
Water pollution represents a significant global challenge, posing a threat to the health and well-being of humans, plants, and animals. The Mediterranean Sea stands out as one of the world's most crucial water bodies, surrounded by nineteen countries and hosting over ten thousand distinct species. This marine ecosystem is vital for millions of people, meeting their nutritional, functional, and recreational needs and serving as a crucial habitat for the nourishment and reproduction of numerous endangered species. Marine pollution results from the introduction of substances or energy into the marine ecosystem through human activities, leading to adverse effects on living resources, endangering human health, and impacting maritime activities. The Mediterranean Sea is anticipated to face substantial impacts due to human activities, with rapid industrial growth and population expansion in coastal regions contributing to the proliferation of domestic and industrial pollutants, thereby creating health, economic, and environmental challenges. Long-term environmental repercussions of unregulated industrial discharges are frequently disregarded in economic assessments concerning costs and benefits. Nonetheless, mounting evidence indicates the accumulation of hazardous industrial by-products in marine organisms. This issue, coupled with the detrimental effects of pollution on recreational pursuits like swimming, surfing, and fishing, raises significant concerns. Industrial wastewater undergoes treatment to eliminate pollutants through diverse methodologies and mechanisms tailored to specific needs. Treatment approaches are categorized into distinct or integrated physical, chemical, and biological methods. Consequently, this paper aims to provide an in-depth examination of marine pollution, its various forms, impacts, and disposal techniques.